A comparison of competitive profiles across the Spanish football leagues - Vales-Vázquez, A.; Casal-López, C.; Gómez-Rodriguez, P.; Blanco-Pita, H. (International Journal of Computer Science in Sport, 2017)
The purpose of this study was to compare the competitive profiles across the Spanish football leagues at the present time. The final standings (n=32) and results of the matches played (n=11,122) in the 2015/2016 season were analysed. Four categories of analysis were selected: Level of competitive balance of matches, Level of compactability of team standings, Magnitude of home-field advantage effect, and Degree of openness of the matches. Using statistical procedures for the comparison of means by analysis of variance (ANOVA) and the Chi-Squared test, it was concluded that in the panorama of Spanish football, the men's 2nd division stands out as the Championship that corresponds to a competitive profile with greater equality and that the women's 1st division presents the most unbalanced competitive profile (p < .05). A trend was also observed that indicated that the more professionalized Championships present a higher level of competitive balance of the matches, a higher level of compactability of the team standings, and a lower degree of openness of the matches with respect to the less professionalized Championships, due to the presence of statistically significant differences (p < .05) in the set of categories analysed.